INCREASING ONLINE SALES FOR SHOPPING NEEDS THROUGH MARKETPLACE IN INDONESIA: GENERATION Z SURVEY ON INDONESIAN MARKET ONLINE - Suryono I.A.; Yacobus A.; Oetomo H. (Russian Journal of Agricultural and Socio-Economic Sciences, 2022)
Information technology in the field of online marketing has succeeded in encouraging the growth of new and old entrepreneurs by taking advantage of the convenience of online marketing, both small and large UMKM (is MSME/Micro, Small and Medium Enterprises) industries, as well as the growth of resellers and dropship. These conditions encourage intense competition among marketplace entrepreneurs in the Indonesian online market. They are competing to get sellers to join the marketplace they manage, they are also competing to get online customers, both in Indonesian and foreign marketplaces in the Indonesian online market. This competition makes marketplaces compete each other to be market leaders or get to the top 5 marketshare marketplaces so that various efforts are made to get closer to customers, with the hope that the marketplace will always be the customer's choice. This study aims to measure the influence of customer e-satisfaction, e-wom and individual personality on repurchase intention of marketplace customers in the Indonesian online market. The population of this study consists of marketplace customers in the online market in Indonesia, with non-probability sampling technique, the sampling uses a purposive sampling method with the criteria that customers have made online purchases at the marketplace at least three times in the last six months, it takes a sample of 304 respondents. The analytical tool used is quantitative path analysis that is used to test the hypothesis. The results of this study indicate that the order of the greatest influence of the variables that form customer e-satisfaction in the marketplace that sells shopping products in the Indonesian online market is customer lifesty, website service quality and trust. Customer e-satisfaction affects the electronic-wom and repurchase intention directly or even when it is moderated by the electronic-wom. The practical implication of this research is a strategy to increase the repurchases intention for online shops, e-commerce, UMKM marketplaces that sell shopping products that can develop the marketing communications through customer life style designs, supported by communicative service quality websites that encourages trust which encourages positive electronic-wom that will eventually encourage the repurchases intention of online shops, e-commerce, UMKM marketplaces in the Indonesian online market.